2017
DOI: 10.1016/j.ajpath.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

miR-182-5p Inhibition Ameliorates Ischemic Acute Kidney Injury

Abstract: Acute kidney injury (AKI) remains a major clinical event with high mortality rates. We previously identified renal miR-182 as the main driver of post-transplantation AKI. Therefore, we tested the causal inference of miR-182 by inhibiting its renal expression in vivo. In 45 rats AKI was induced by right nephrectomy and contralateral clamping of the renal pedicle for 40 minutes. Systemically administered antisense oligonucleotide (ASO) inhibited miR-182 in the kidneys up to 96 hours. The maximum creatinine eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…We and others further identified the microRNA species with significant changes in expression during ischemic AKI (24,25). More recent studies have examined the role and regulation of some of these microRNAs in ischemic AKI, including miR-494, -21, -126, -687, -150, -489, and -17-5p (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Interestingly, some of the microRNAs promote ischemic AKI, but others play renoprotective roles (32,36,40).…”
Section: Hif-1 Mediates Mir-668 Induction In Ischemic Akimentioning
confidence: 82%
“…We and others further identified the microRNA species with significant changes in expression during ischemic AKI (24,25). More recent studies have examined the role and regulation of some of these microRNAs in ischemic AKI, including miR-494, -21, -126, -687, -150, -489, and -17-5p (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Interestingly, some of the microRNAs promote ischemic AKI, but others play renoprotective roles (32,36,40).…”
Section: Hif-1 Mediates Mir-668 Induction In Ischemic Akimentioning
confidence: 82%
“…LETO (n = 13), OLETF (n = 12), CQ-treated LETO (LETO+CQ, n = 9), and CQ-treated OLETF (OLETF+CQ, n = 10) underwent nephrectomy of the right kidney followed by 30-min ischemia/24 h-reperfusion in the left kidney. We employed this one-kidney one-I/R model as in earlier studies 3234 because, in pilot experiments, bilateral renal I/R resulted in a large data variation between experiments in our hands (data not shown). The unilateral renal I/R method has an advantage that the right kidney removed before I/R of the contralateral kidney serves as control tissue before I/R.…”
Section: Resultsmentioning
confidence: 99%
“…38 Other strategies at the pre-clinical stage targeting donor organs rather than the recipients focused on cell-bound complement, 39 coagulation inhibitors, 40 and the use of antisense nucleotides for amelioration of ischemia-reperfusion injury. 41,42 A recent donor intervention trial from the US found that the induction of mild hypothermia in the DBD reduces delayed graft function after kidney transplantation. 43 Preliminary observational data suggest that low-dose dopamine may provide an additive effect to the benefit of a lower core body temperature.…”
Section: Molecul Ar Mechanis Ms Of Protec Ti Onmentioning
confidence: 99%